Posterior ankle arthroscopy: current state of the art. Issue 5 (7th August 2017) - Van Dijk, C Niek; Vuurberg, Gwendolyn; Batista, Jorge; d'Hooghe, Pieter
Abstract : The most common hindfoot pathologies seen in clinical practice and sports medicine are posterior ankle impingement and osteoarthrosis (OA). Both these—and other pathologies such as insertional tendinitis and Haglund's disease—may cause significant disability, in both everyday life and during sporting activities. Post-traumatic OA alone causes a healthcare burden of over 3 billion US dollars per year. An adequate approach of these pathologies is required to minimise this healthcare burden and additionally to maintain patients' economic productiveness. The aim of this article is to outline the most important evidence-based indications concerning posterior ankle arthroscopy focusing on diagnostics, surgical techniques, complications, geographical differences and future developments in the field of hindfoot arthroscopy. Initially, the treatment of hindfoot pathology is conservative. If adequate conservative treatment does not result in a good response, surgery may be indicated. Over the last three decades, arthroscopy of the ankle joint has become a standardised and important procedure, with numerous indications for both anterior and posterior pathology. Since 2000, a two-portal hindfoot arthroscopic approach has been described and used globally in clinical practice. Some of the indications that may be addressed using this approach are the treatment of posteriorly located osteochondral defects, posterior ankle impingement, pathology of the deep portion of the deltoid ligament, Cedell fracture, tarsal tunnel release, loose bodies and tibiotalar or subtalar arthrodesis. Tendon pathology can also be treated using posterior portals; however, this is beyond the scope of this review.